American Religion : Contemporary Trends - Chaves, Mark (Book collections on Project MUSE., 2011)
Most Americans say they believe in God, and more than a third say they attend religious services every week. Yet studies show that people do not really go to church as often as they claim, and it is not always clear what they mean when they tell pollsters they believe in God or pray. American Religion presents the best and most up-to-date information about religious trends in the United States, in a succinct and accessible manner. This sourcebook provides essential information about key developments in American religion since 1972, and is the first major resource of its kind to appea.